Genome-Wide Identification of Cellular Pathways and Key Genes That Respond to Sodium Bicarbonate Stress in Saccharomyces cerevisiae - Cao, Xiuling; An, Tingting; Fu, Wenhao; Zhang, Jie; Zhao, Huihui; Li, Danqi; Jin, Xuejiao; Liu, Beidong (Frontiers in Microbiology, 2022)
Sodium bicarbonate (NaHCO3) is an important inorganic salt. It is not only widely used in industrial production and daily life, but is also the main stress in alkaline saline soil. NaHCO3 has a strong ability to inhibit the growth of fungi in both natural environment and daily application. However, the mechanism by which fungi respond to NaHCO3 stress is not fully understood. To further clarify the toxic mechanisms of NaHCO3 stress and identify the specific cellular genes and pathways involved in NaHCO3 resistance, we performed genome-wide screening with NaHCO3 using a Saccharomyces cerevisiae deletion mutant library. A total of 33 deletion mutants with NaHCO3 sensitivity were identified. Compared with wild-type strains, these mutants had significant growth defects in the medium containing NaHCO3. Bioinformatics analysis found that the corresponding genes of these mutants are mainly enriched in the cell cycle, mitophagy, cell wall integrity and signaling pathways. Further study using transcriptomic analysis showed that 309 up-regulated and 233 down-regulated genes were only responded to NaHCO3 stress, when compared with yeast transcriptomic data under alkaline and saline stress. Up-regulated genes were mainly concentrated in amino acid metabolism, steroid biosynthesis, and cell wall, while down-regulated genes were enriched in various cellular metabolisms. In summary, we have identified the cellular pathways and key genes that respond to NaHCO3 stress in the whole genome, providing resource and direction for understanding NaHCO3 toxicity and cellular resistance mechanisms.